Bioactives From Probiotic For Dermal Health Upon Physical Treatments - Lew, Lee Ching (2013)
Lactobacilli and bifidobacteria are the most common genera of probiotics with documented potentials on gut health. Recent studies suggested that such potentials can be extended beyond gut well-being, such as that of dermal health. This study was aimed to evaluate the production of bioactives that are essential for skin health from either lactobacilli or bifidobacteria grown in milk. Lipoteichoic acid content in the cell wall fraction was higher (P < 0.05) in Lactobacillus rhamnosus FTDC 8313 and Bifidobacterium longum BL 8643 compared to the other strains studied. Meanwhile, all strains studied showed equal concentration of cell wall peptidoglycan. Our results showed that lactobacilli produced higher concentration of hyaluronic acid and diacetyl than bifidobacteria. Strains of lactobacilli and bifidobacteria studied also produced acid and neutral sphingomyelinase (SMase), enzymes that generate ceramides which subsequently play important roles in development of physical barriers in the stratum corneum (SC). Sphingomyelinase activity in L. rhamnosus FTDC 8313 was also optimized using divalent metal ions via response surface methodology. Using a full-factorial design for factors screening, only magnesium sulphate (MgSO4) and manganese sulphate (MnSO4) significantly (P < 0.001) influenced SMase activity while the effects of calcium sulphate (CaSO4) was insignificant (P > 0.05).